Screening and the analysis of genotypic and phenotypic characterization of glucose-6-phosphate dehydrogenase (G6PD) deficiency in Fujian province, China - Zhou, Jinfu; Zeng, Yinglin; Tang, Jianping; Chen, Shihong; Li, Guilin; Qiu, Xiaolong; Zhao, Peiran; Huang, Ting; Luo, Jinying; Lin, Na; Xu, Liangpu (Frontiers in Genetics, 2024)
Introduction: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is a common X-linked hereditary disorder in Southern China. However, the incidence rate of G6PD deficiency and the frequency of the most common G6PD gene variants vary widely. This study aimed to investigate the prevalence, genotype, and phenotypic features of G6PD deficiency in neonates in Fujian province, Southeastern China. Methods: This retrospective cohort study enrolled 2,789,002 newborns (1,521,431 males and 1,267,571 females) based on the newborn screening program for G6PD deficiency in Fujian Province between January 2010 and December 2021. Results: Of the 2,789,002 newborns enrolled, 26,437 were diagnosed with G6PD deficiency (22,939 males and 3,498 females), with an estimated prevalence of 0.95% in the Fujian province The prevalence was significantly higher among males (1.51%) than among females (0.28%) (P<0.00001). Among the 3198 patients with G6PD deficiency, 3092 cases (2145 males and 947 females) were detected to have G6PD gene variants. The top 6 prevalent genotypes identified represented 90.84% (2095/3198) of the total and included c.1376G>T (44.93%), c.1388G>A (18.42%), c.1024C>T (9.32%), c.95A>G (8.69%), c.392G>T (5.25%), and c.871G>A (4.22%). The frequency of genotypes with c.1388G>A, c.1024C>T, and c.871G>A was higher in males than in females in the Fujian province, while the frequency of genotypes with c.1376G>T was lower. Furthermore, when comparing the enzyme activities of the top six prevalent genotypes, significant differences were observed in the enzyme activities among the genotypes of male hemizygotes and female heterozygotes. According to the new classification of G6PD variants proposed by the World Health Organization (WHO), variants with c.1376G>T, c.95A>G, and c.871G>A were recognized as Class A, while the c.392G>T, c.1388G>A, and c.1024C>T were recognized as Class B. Discussion: To the best of our knowledge, this study is the first to systematically describe the overview of epidemiological characteristics of newborn G6PD deficiency in the Fujian province, China, including the screening rate, incidence rate, and variant spectrum. Additionally, we elucidated the relationship between the distribution of enzyme activity with specific mutations and their WHO classification patterns. Our results could provide strategies for screening, diagnosis, and genetic counseling of G6PD deficiency in this area.